2007
DOI: 10.1017/s0263034607000158
|View full text |Cite
|
Sign up to set email alerts
|

High energy density physics problems related to liquid jet lithium target for Super-FRS fast extraction scheme

Abstract: The new international facility for antiproton and ion research (FAIR), at Darmstadt, Germany, will accelerate beams of all stable isotopes from protons up to uranium with unprecedented intensities (of the order of 10 12 ions per spill). Planned future experiments include production of exotic nuclei by fragmentation/fission of projectile ions of different species with energies up to 1.5 GeV/u at the proposed super conducting fragment separator, Super-FRS. In such experiments, the production target must survive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It is therefore concluded that one can use a solid graphite target for the fast extracted heavy ion beams at the Super -FRS target and it may not be necessary to develop a liquid jet target (Tahir et al, 2007e). PIRIZ, A.R., TAHIR, N.A., LOPEZ CELA, J.J., CORTAZAR, O.D Solid graphite target for high intensity fast extracted uranium beams for the Super-FRS 17…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore concluded that one can use a solid graphite target for the fast extracted heavy ion beams at the Super -FRS target and it may not be necessary to develop a liquid jet target (Tahir et al, 2007e). PIRIZ, A.R., TAHIR, N.A., LOPEZ CELA, J.J., CORTAZAR, O.D Solid graphite target for high intensity fast extracted uranium beams for the Super-FRS 17…”
Section: Discussionmentioning
confidence: 99%
“…The equation of state (EOS) describes a physical system by the relation between its thermodynamic quantities, such as pressure, energy, density, entropy, specific heat, etc., and is related to both fundamental physics and the applied sciences (Lomonosov, 2007;Tahir et al, 2007aTahir et al, , 2007bTahir et al, , 2007cTahir et al, , 2008aTahir et al, , 2008bLebo et al, 2008). Local thermodynamic equilibrium of nature can be described by a wide range of EOS pressure, density, and temperatures.…”
Section: Introductionmentioning
confidence: 99%